Evaluation of the Appropriateness of Medication Use in Outpatients with Depression at Radjiman Wediodiningrat Mental Hospital, Lawang, Malang Regency, in 2024 - Hajar Sugihantoro; Puspita Rahma Qurrota'aini; Eko Denny Wahyudi (Universitas Pahlawan Tuanku Tambusai, 2026)
Depression is a mood disorder characterized by profound feelings of sadness. It frequently occurs across various societal strata and is a leading factor contributing to suicide. Multiple therapeutic approaches are available for treating depression, including antidepressants, antipsychotics, anxiolytics, and anticholinergics. However, the use of psychotropic drug combinations often lacks precision. This study aims to analyze the drug utilization profile and assess the appropriateness of medication use in outpatient depression patients at Dr. Radjiman Wediodiningrat Mental Hospital, Lawang, in 2024, focusing on correct indication, patient suitability, drug selection, and dosing accuracy. Data were collected retrospectively from medical records of depression patients in 2024, using a probability sampling technique. A total of 94 medical records met the inclusion criteria. The obtained data is evaluated for its precision based on therapy guidelines. The research results on drug use profiles show that the most commonly used drug therapy combination is antidepressants with antipsychotics and anxiolytics, at 36%.of prescriptions. Evaluation of drugs use revealed that 100% were appropriate in terms of indication, 100% were suitable for the patient, 93.6% were appropriate in drug selection, and 96% had accurate dosing.